Head-to-head comparison of biological drugs for inflammatory bowel disease: from randomized controlled trials to real-world experience. (May 2021) - Macaluso, Fabio Salvatore; Maida, Marcello; Grova, Mauro; Crispino, Federica; Teresi, Giulia; Orlando, Adele; Orlando, Ambrogio
During past years, the increasing knowledge of molecular mechanisms of inflammatory bowel disease (IBD) have led to the development of several targeted biological therapies. This great expansion of available medical options has prompted the need for comparative data between drugs. For years, given that most randomized controlled trials (RCTs) were performed only versus placebo, this demand has clashed with the absence of head-to-head trials comparing two or more treatments. The quality of evidence coming from real-world experience was low overall, so it was extremely difficult to clarify the correct positioning of the biologicals inside the therapeutic algorithms for IBD. Fortunately, times are changing: head-to-head comparative RCTs have been conducted or are ongoing, and the methodological quality of real-world studies is gradually increasing, mainly thanks to a higher rate of application of statistical methods capable of reducing the selection bias, such as the propensity score. In this evolving scenario, the increasing number of comparative RCTs is providing high-quality data for a correct drug positioning in IBD. In parallel, real-world observational studies are supporting the data coming from RCTs, and covering those comparisons not performed in the RCT setting. We believe that there is moderate evidence already available to support clinicians in the correct choice between different biologicals, and data will certainly be more robust in the near future.